Sustaining nonprofit performance : the case for capacity building and the evidence to support it - Light, Paul Charles (Brookings Institution Press, 2004)
America's nonprofit organizations are facing an uncertain future. Many are operating with leaner budgets and face a wave of budget cuts as the federal deficit grows. At the same time, public confidence in nonprofits is at a contemporary low. Congress seems poised to enact new and stringent rules for nonprofit spending.